Théoriser l’action publique urbaine et territoriale : éléments pour une épistémologie de l’aménagisme - Philippe Genestier (Métropoles, 2019)
What pillars underpin city planning and development? What socio-historical vision sets its mission and lends it legitimacy? How does urbanism achieve credibility and social acceptability? This text seeks to provide some answers to these theoretical and epistemological questions by analysing the narratives developed in the field by the different stakeholders involved in and on the urban space.